(untitled) (Contemporary Mathematics, 2024)
United Nations’ Human Development Index measures human development and has significant positive correlation with abundance in natural resource. Data Envelopment Analysis is used for composite indicators’ development and overcomes weighting techniques’ limitations. It has limitations in existence of missing records that Goal Programming can overcome. Accordingly, this paper introduces a new Human Development Index that improves upon the United Nations’ Human Development Index by incorporating natural resource abundance and addressing missing data issues through Goal Programming. To address these issues, a model is proposed that combines Data Envelopment Analysis and Goal Programming. The model first estimates missing values and then calculates weights for the Human Development Index using Data Envelopment Analysis, which integrates standardized human development dimensions with natural resource factors. This revised Human Development Index results in new country rankings and is validated through a correlation analysis with the United Nations’ Human Development Index and a Wilcoxon Signed-Rank test. The correlation analysis shows strong agreement in rankings despite different weighting methods, while the Wilcoxon test indicates significant differences in median rankings. Our proposed index offers a more comprehensive measure of human development by considering both human development dimensions and natural resources, enhancing the accuracy of the Human Development Index and suggesting areas for future research into additional factors affecting human development, beside others.